Planning community-based intervention for speech for children with cleft lip and palate from rural South India: A needs assessment - Subramaniyan Balasubramaniyan; Vaidyanathan Raghunathan; B. Rajashekhar; B. W. C. Sathiyasekaran; Roopa Nagarajan (Indian Journal of Plastic Surgery)
Background and Aim: A community-based rehabilitation programme, Sri Ramachandra University-Transforming Faces project, was initiated to provide comprehensive management of communication disorders in individuals with CLP in two districts in Tamil Nadu, India. This community-based programme aims to integrate hospital-based services with the community-based initiatives and to enable long-term care. The programme was initiated in Thiruvannamalai (2005) district and extended to Cuddalore (2011). The aim of this study was to identify needs related to speech among children with CLP, enroled in the above community-based programme in two districts in Tamil Nadu, India. Design: This was a cross–sectional study. Participants and Setting: Ten camps were conducted specifically for speech assessments in two districts over a 12-month period. Two hundred and seventeen individuals (116 males and 101 females) >3 years of age reported to the camps. Methods: Investigator (SLP) collected data using the speech protocol of the cleft and craniofacial centre. Descriptive analysis and profiling of speech samples were carried out and reported using universal protocol for reporting speech outcomes. Fleiss’ Kappa test was used to estimate inter-rater reliability. Results: In this study, inter-rater reliability between three evaluators revealed good agreement for the parameters: resonance, articulatory errors and voice disorder. About 83.8% (n = 151/180) of the participants demonstrated errors in articulation and 69% (n = 124/180) exhibited abnormal resonance. Velopharyngeal port functioning assessment was completed for 55/124 participants. Conclusion: This study allows us to capture a “snapshot” of children with CLP, living in a specific geographical location, and assist in planning intervention programmes.